Crystal structure of 2-(4-methylphenyl)-2-oxo-1-(phenyliodonio)-1-(triphenylarsonio)ethanid tetrafluoroborate solved from X-ray powder data - Mironov, Andrei V.; Chernyshev, Vladimir V.; Matveeva, Elena D.; Podrugina, Tatyana A.; Alferova, Vera A.; Gleiter, Rolf; Zefirov, Nikolai S. (Zeitschrift für Kristallographie. Crystalline materials, 2013)
The crystal structure of 2-(4-methylphenyl)-2-oxo-1-(phenyliodonio)-1-(triphenylarsonio)ethanid tetrafluoroborate, C 33 H 27 AsIO+BF 4 - , was solved and refined from laboratory X-ray powder diffraction data in combination with a DFT calculation (Co K α1 , a =24.427(2) Å, b = 13.3412(18) Å, c =22.399(2) Å, β = 119.49(2)°, S.G. C2/c , R p / R wp = 0.030/0.039). The main features of the C 33 H 27 AsIO+BF 4 - structure are similar to those reported previously for arsenium and phosphorous organic compounds. The distinctive features are short I … O and I … F (2.743(19) and 2.916(17) Å, respectively) intermolecular contacts, also observed previously in the same type of compound, refined from single crystal data
Gesehen am 25.05.2021